Compound-specific isotope analysis (CSIA) of micropollutants in the environment — current developments and future challenges. (October 2016) - Elsner, Martin; Imfeld, Gwenaël
Graphical abstract: Highlights: CSIA bears great potential to evaluate micropollutant degradation in the environment. We review analytical challenges for CSIA of low concentration, polar micropollutants. We address current applications and prospects of micropollutant CSIA in the field. We provide an outlook to identify micropollutants sources and quantify transformation. Abstract : Over the last decade, the occurrence of micropollutants in the environment has become a worldwide issue of increasing concern. Compound-specific stable-isotope analysis (CSIA) of natural isotopic abundance may greatly enhance the evaluation of sources and transformation processes of micropollutants, such as pesticides, personal care products or pharmaceuticals. We summarize recent advances from laboratory studies, review current limitations and analytical challenges associated with low concentrations and high polarity of micropollutants, and delineate the potential of micropolluant CSIA for field applications. We highlight future challenges and prospects regarding source apportionment, identification of biotic and abiotic transformation reactions on a mechanistic level, as well as integrative evaluation of degradation hot spots on the catchment scale. Such advances may feed into a framework for risk assessment of micropollutants that includes CSIA.